METHODOLOGY OF AHLUS SUNNAH WAL JAMAAH IN WRITING THE HISTORY OF ISLAMIC CULTURE - Imam Tabroni; Arifin Saefulloh (Jurnal Riset Rumpun Agama dan Filsafat, 2022)
The method of writing the history of Ahlus Sunnah wal Jama'ah is to rely on syar'i sources and prioritize it from other sources, must be based on correct Islamic creed, understand the condition of historical objects and ensure their truth, topics about a nation must be based on fair and inshaf fact , use the science of jarh wat ta'dil in tying up several contradictory narrations, referring to the books of hadith, especially in the early events of Islam, being careful in quoting from the books of heretics and non-Muslim books, paying attention to the conditions at the time of the events, use Islamic terms.